Degradation of phenol by catalytic ozonation - P., Yogeswary (Faculty of Chemical and Natural Resources Engineering, UTM, 2007)
The performance of a metal-based zeolite catalyst (Fe-ZB) was investigated by ozonation process under different experimental variables such as the ozone flow rate, mass and metal weight percent impregnated in the catalyst, temperature, initial pH, concentration and the volume of phenol solution to be treated. The degradation of phenol in the study was determined using HPLC method. In addition, the degree of degradation was also determined indirectly through Chemical Oxygen Demand (COD) and Total Organic Carbon (TOC) of the samples. It was observed that a smaller percentage of metal loading catalyst resulted in a higher degradation of phenol compared to those with higher metal loading catalyst. As expected, the degradation of phenol increases with ozone flow rates and mass of catalyst. Interestingly, the degradation of phenol was significantly high under basic condition where the degradation was almost completed i.e. 98.1% at initial phenol solution of pH 11. On the contrary, the degradation of phenol decreases with increasing temperature, concentration and volume of phenol solution.